Researches regarding the influence of the unconventional soil tillage systems upon weeding and soybean yield, in pedoclimate conditions in the transylvanian plain - Felicia Cheţan; Cornel Cheţan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The importance of soybeans derives from the multiple uses in the human nutrition, animal feeding, industry, but also as a plant that improves the physical properties of the soil by improving the soil in nitrogen. Regardless of the use of practical cultures, for obtaining high yield in terms of quantity and quality, a particularly important role for all other technological links, can be to fight the weeds. Soybeans are sensitive to weeding the first stages of vegetation until the plants can reach the ground cover and at the maturation after the leaves start to fall. In this paper we present the weeding degree and the soybean yield realized, under the influence of unconventional tillage systems and climatic conditions from 2018-2019. In unconventional systems the number of annual monocotyledonous species decreases but the number of perennial weeds increases. As an alternative to the classical system, soybeans can be grown in a minimum tillage system (tillage with chisel), the difference in yield between the classical system is insignificant (only 16 kg/ha).
Keywords: Q01; Q15; Q16; 330; tillage system; clime; weeds; soybean; yield